Insertion into Geostationary Orbit of a Spacecraft with Diffractive Orbit by Low Torque Electric Propulsion. (2017) - Soyfer, V.A.; Salmin, V.V.; Karpeev, S.V.; Chetverikov, A.S.; Peresypkin, K.V.; Tkachenko, I.S.
Abstract: The paper solves the problem of control over and insertion into geostationary orbit of a spacecraft with diffractive optical elements with the help of low torque electric propulsion (EP). Main features of a design layout of a spacecraft with diffractive optics and the requirements for inserting such spacecraft into geostationary orbit are discussed. The prototype of such system is the MOIRE project spacecraft. The paper suggests a three-stage ballistic insertion scheme: lifting to near Earth orbit by a launch vehicle, transfer to intermediate orbit with the help of acceleration module, and at the final stage the spacecraft is transferred from intermediate to geostationary orbit by low thrust electric propulsion system.